2022
DOI: 10.1002/pchj.552
|View full text |Cite
|
Sign up to set email alerts
|

The mediating role of alexithymia and cognitive flexibility in the relationship between behavioral inhibition system/behavioral activation system and depression in Turkish population

Abstract: This study aims to examine the relationships between the behavioral inhibition system (BIS)/behavioral activation system (BAS), depression, cognitive flexibility, and alexithymia, and to determine the mediator role of cognitive flexibility and alexithymia in the relationship between BIS/BAS and depression. Data were collected from a community sample, consisting of 1,275 people, 904 women (70.90%) and 371 (29.10%) men, aged 18–65 years. It was detected that the whole variables in this research were interrelated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 48 publications
(61 reference statements)
0
2
0
Order By: Relevance
“…Previous study has shown that people with alexithymia and healthy people have different beliefs regarding emotionally induced events, with those with alexithymia being more prone to hold negative beliefs about past events and interpret the present fatalistically [ 34 ]. Although there is no definitive conclusion about the mechanism of alexithymia, a number of studies have demonstrated that people with alexithymia have a degree of cognitive impairment [ 35 , 36 ], particularly a lack of cognitive flexibility, which makes it difficult to appropriately identify and give feedback to social emotions [ 37 ]. From the perspective of REBT mechanism of action, REBT can change the irrational beliefs of older people by intervening with their cognition and belief, so reducing their negative feelings about life events, thereby enabling a fundamental change in the occurrence and development of alexithymia.…”
Section: Discussionmentioning
confidence: 99%
“…Previous study has shown that people with alexithymia and healthy people have different beliefs regarding emotionally induced events, with those with alexithymia being more prone to hold negative beliefs about past events and interpret the present fatalistically [ 34 ]. Although there is no definitive conclusion about the mechanism of alexithymia, a number of studies have demonstrated that people with alexithymia have a degree of cognitive impairment [ 35 , 36 ], particularly a lack of cognitive flexibility, which makes it difficult to appropriately identify and give feedback to social emotions [ 37 ]. From the perspective of REBT mechanism of action, REBT can change the irrational beliefs of older people by intervening with their cognition and belief, so reducing their negative feelings about life events, thereby enabling a fundamental change in the occurrence and development of alexithymia.…”
Section: Discussionmentioning
confidence: 99%
“…Previous study has shown that people with alexithymia and healthy people have different beliefs regarding emotionally induced events, with those with alexithymia being more prone to hold negative beliefs about past events and interpret the present fatalistically [34]. Although there is no de nitive conclusion about the mechanism of alexithymia, a number of studies have demonstrated that people with alexithymia have a degree of cognitive impairment [35,36], particularly a lack of cognitive exibility, which makes it di cult to appropriately identify and give feedback to social emotions [37]. From the perspective of REBT mechanism of action, REBT can change the irrational beliefs of the elderly by intervening with their cognition and belief, so reducing their negative feelings about life events, thereby enabling a fundamental change in the occurrence and development of alexithymia.…”
Section: Discussionmentioning
confidence: 99%